ANALISIS PENGARUH BELANJA MODAL, INDEKS PEMBANGUNAN MANUSIA, DAN TENAGA KERJA TERSERAP TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI INDONESIA - Wawan Aryanto; Riya Dwi Handaka (Jurnal Akuntansi Manajerial (Managerial Accounting Journal), 2018)
There are many ways for a region to raise its economic growth. On this research aims to examine the effect of Human Development Index, capital expenditures, and labor absorption on economic growth of local governments in Indonesia. We use secondary data. There are variable the Human Development Index, capital expenditures of local governments, and labor absorption as an exogenous variable, while Gross Regional Domestic Product as an endogenous variable. This study uses panel data which combines time series data and cross section. These data were analyzed using regression with Eviews program. The results with significance level α = 0.05 showed that all hypothesis are accepted. All of exogenous variables are proved significantly positive effect on economic growth.